2011
DOI: 10.1007/s00531-011-0683-x
|View full text |Cite|
|
Sign up to set email alerts
|

Tectonometamorphic evolution of the Permo-Triassic Songrim (Indosinian) orogeny: evidence from the late Paleozoic Pyeongan Supergroup in the northeastern Taebaeksan Basin, South Korea

Abstract: The deformed and metamorphosed middle Pennsylvanian to Early Triassic (?) rocks of the Pyeongan Supergroup, occurring in northeastern flank of the Paleozoic Taebaeksan Basin, east central South Korea, record the impact of the Late Permian-Triassic Songrim (Indosinian) collisional orogeny in the eastern Eurasia margin. Analysis of meso-and microstructures and their relationship with porphyroblast growth has revealed that these metasedimentary rocks were affected by four deformation events (D 1 -D 4 ). During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…예를 들어, 서부경기지괴의 홍성 및 태안지역의 서산층군 과 태안층의 연대 (Cho et al, 2010)가 규명되고 있 고, 옥천대 남서부 지역의 경계부인 영광도폭내 시대 미상 저변성 퇴적암이 전기 데본기 이후에 퇴적된 고 생대 퇴적층임이 밝혀졌다 (Ha et al, 2014). 또한, 태백산분지의 만항층과 사동층에 대한 SHRIMP UPb 연대가 규명되면서 평안누층군 기저의 퇴적시기 하한과 범위도 최근 규명되기 시작하였다 (Kim et al, 2012;Lee et al, 2010). 만항층의 저어콘 U-Pb 연 대 결과는 방추충에 의한 생층서와 잘 일치한다 (Cheong, 1969(Cheong, , 1973Park, 1996).…”
Section: 최성자·김동연·조등룡·김유봉unclassified
“…예를 들어, 서부경기지괴의 홍성 및 태안지역의 서산층군 과 태안층의 연대 (Cho et al, 2010)가 규명되고 있 고, 옥천대 남서부 지역의 경계부인 영광도폭내 시대 미상 저변성 퇴적암이 전기 데본기 이후에 퇴적된 고 생대 퇴적층임이 밝혀졌다 (Ha et al, 2014). 또한, 태백산분지의 만항층과 사동층에 대한 SHRIMP UPb 연대가 규명되면서 평안누층군 기저의 퇴적시기 하한과 범위도 최근 규명되기 시작하였다 (Kim et al, 2012;Lee et al, 2010). 만항층의 저어콘 U-Pb 연 대 결과는 방추충에 의한 생층서와 잘 일치한다 (Cheong, 1969(Cheong, , 1973Park, 1996).…”
Section: 최성자·김동연·조등룡·김유봉unclassified
“…Source rocks for the lower part of the Pyeongan Supergroup were assumed to be sedimentary and low‐grade metamorphic rocks (Y. I. Lee & Sheen, ; Yu et al, ), which possibly correspond to the basement rocks (mostly of Precambrian metamorphic rocks) of the Inner Mongolia Paleo‐uplift. However, recent discoveries of Upper Carboniferous zircon grains from the Manhang Formation (H. S. Kim, Ree, & Kim, ; Z. Li, Peng, Xu, Han, & Zhai, ) suggest that, in places, exhumation of the Inner Mongolia Paleo‐uplift occurred at a more accelerated rate: Z. Li et al () obtained detrital zircon age spectra of the Manhang sandstone with two major age clusters at 358–288 Ma and 1.89–1.78 Ga, whilst H. S. Kim et al () report SHRIMP U–Pb detrital zircon ages of 330–310 Ma from metapelites of the Manhang Formation. Sediments of the middle part (Gohan Formation) were suggested to have been derived from an area with diorite, granodiorite, acidic volcanic rocks, and metamorphic rocks (Yu et al, ) which can be equated with the Late Carboniferous diorite‐granodiorite suite of the Inner Mongolia Paleo‐uplift (S‐H.…”
Section: Late Paleozoic Sedimentation In a Retroarc Foreland Basinmentioning
confidence: 99%
“…H. S. Kim et al () also suggested that the Pyeongan Supergroup was deposited in an arc‐related foreland basin at an active continental margin in the late Paleozoic, based on SHRIMP U–Pb detrital zircon ages of 330–310 Ma from the Manhang Formation. Y. I. Lee and Sheen () and H. S. Kim et al () attempted to relate the Pyeongan Supergroup to the upper Paleozoic terranes of Japan: Y. I. Lee and Sheen () suggested the upper Paleozoic Akiyoshi orogen as a candidate for provenance of the Pyeongan Supergroup, whereas H. S. Kim et al () correlated the Pyeongan Supergroup with the upper Paleozoic metamorphic rocks of the Hida‐Oki Belt based on the late Paleozoic (340−320 Ma) magmatic events of the Hida‐Oki Belt (Arakawa, Saito, & Amakawa, ).…”
Section: Late Paleozoic Sedimentation In a Retroarc Foreland Basinmentioning
confidence: 99%
See 2 more Smart Citations